Free pregnancy-associated plasma protein-A as a biomarker of abnormalities during pregnancy - Tiittanen, Vilma (My University, 2022)
Low level of pregnancy-associated plasma protein-A (PAPP-A) in serum during pregnancy is associated with pregnancy abnormalities, such as Down’s syndrome, miscarriage and ectopic pregnancy. PAPP-A exist in two different forms in circulation, as a complexed form with its inhibitors and as a free and active form (fPAPP-A). It has been suggested that in the first trimester of pregnancy significant proportion of PAPP-A is found in the circulation in free form (even 30 %), but currently used commercial assays measure PAPP-A that includes both complex and free form. The aims of this study were to determine the levels of fPAPP-A in the first trimester of normal pregnancy, to examine whether fPAPP-A is associated with miscarriage, and to compare fPAPP-A and PAPP-A as predictors of the risk of miscarriage. A serum sample panel (n=196), including individuals with normal pregnancy (n=159) and women who miscarried (n=37), was analysed with a unique immunoassay, which measures only the free form of PAPP-A. The used immunoassay was developed at the Biotechnology Unit of the University of Turku. This immunoassay utilizes fPAPP-A specific capture antibody and a tracer antibody, which recognizes both PAPP-A forms. It was discovered that fPAPP-A serum levels increased throughout the first trimester in both normal pregnancies and miscarried pregnancies, but in miscarried pregnancies fPAPP-A serum levels were statistically significantly lower. Surprisingly, only a small fraction (on average 2-3 %) of PAPP-A was in free form throughout the first trimester. Both fPAPP-A and PAPP-A were able to discriminate miscarried pregnancies from normal pregnancies equally well. Maternal age, BMI and smoking status were only weakly associated with fPAPP-A serum concentration.
Keywords: fPAPP-A, pregnancy, miscarriage